Delivering E-governance services in Bangladesh through Libraries and Information Centers: Realities, Challenges and Possibilities - Islam, M. Monirul; Sunvy, Ahmed Shafkat (Journal of Information and Knowledge, 2024)
Bangladesh is trying to achieve Smart Bangladesh Vision 2041 to put the country on a new, sustainable path of growth while also serving as a role model for other developing nations. With that goal in mind, the government is trying to introduce e-governance services in every government sector. This study looks into user perspectives, obstacles, and suggestions for offering e-governance services through libraries and information centres. A proposed e-governance service delivery model for public libraries is also presented in this paper.